Road Safety Situation of Hungary Reflected by National and International Objectives - Holló, P. (Acta Technica Jaurinensis, 2011)
Between the years 2001 and 2009 in Hungary and in all EU member states the number of fatalities resulting from road accident decreased by 34% and 36%, respectively. In 2008 a real breakthrough was achieved in road safety improvement, which continued in 2009 and in 2010, too. The breakthrough (2008) was mainly the result of consistent and strict measures (socalled “objective” responsibility (owners’ liability) , “zero-tolerance” against drinking and driving, rendering more stringent demerit point system, automated speed cameras, etc.), admitting that economic recession also contributed to this improvement, especially in 2009, but in 2010, too, although in a lesser extent. During evaluation a special attention should be paid to the methodological questions as well (e.g. the difference between the 48-hour- and the 30-day-outcome.)